2023
DOI: 10.15587/1729-4061.2023.275984
|View full text |Cite
|
Sign up to set email alerts
|

Applying machine learning to improve a texture type image

Abstract: The paper is devoted to machine learning methods that focus on texture-type image enhancements, namely the improvement of objects in images. The aim of the study is to develop algorithms for improving images and to determine the accuracy of the considered models for improving a given type of images. Although currently used digital imaging systems usually provide high-quality images, external factors or even system limitations can cause images in many areas of science to be of low quality and resolution. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…After classification into road image subclasses, the AttentiveGAN submodel [19] is passed through, which detects and cleans images of noise such as snow marks, raindrops, and fog. Image classification [20] Other medical and space imaging classes go through the super-resolution generative adversarial network (SRGAN) submodel [21]- [23]. It performs image enhancement using generative adversarial networks (GANs).…”
Section: Methodsmentioning
confidence: 99%
“…After classification into road image subclasses, the AttentiveGAN submodel [19] is passed through, which detects and cleans images of noise such as snow marks, raindrops, and fog. Image classification [20] Other medical and space imaging classes go through the super-resolution generative adversarial network (SRGAN) submodel [21]- [23]. It performs image enhancement using generative adversarial networks (GANs).…”
Section: Methodsmentioning
confidence: 99%
“…This paper focuses on two important methods within GANs: pixel-to-pixel (Pix2Pix) [6], [7] and regular GAN [8]- [10]. Pix2Pix, which is based on the idea of learning from paired data before and after transformation, is a powerful tool for creating high-quality images [11]- [13]. In this study, we analyze the dynamics of the losses of the generator and discriminator during the training process, the features of convergence, and the stability of this method.…”
Section: Introductionmentioning
confidence: 99%
“…Tussupov et al [16] presents a unique learning-based approach to denoising without the use of pure data. The authors have shown that deep neural networks can be trained with a pair of noisy images without the need for pure training data.…”
Section: Introductionmentioning
confidence: 99%